Identification of mouse cochlear progenitors that develop hair and supporting cells in the organ of Corti - Xu, Jinshu; Ueno, Hiroo; Xu, Chelsea Y.; Chen, Binglai; Weissman, Irving L.; Xu, Pin-Xian (Nature communications, 2017)
The adult mammalian cochlear sensory epithelium houses two major types of cells, mechanosensory hair cells and underlying supporting cells, and lacks regenerative capacity. Recent evidence indicates that a subset of supporting cells can spontaneously regenerate hair cells after ablation only within the first week postparturition. Here in vivo clonal analysis of mouse inner ear cells during development demonstrates clonal relationship between hair and supporting cells in sensory organs. We report the identification in mouse of a previously unknown population of multipotent stem/progenitor cells that are capable of not only contributing to the hair and supporting cells but also to other cell types, including glia, in cochlea undergoing development, maturation and repair in response to damage. These multipotent progenitors originate from Eya1 -expressing otic progenitors. Our findings also provide evidence for detectable regenerative potential in the postnatal cochlea beyond 1 week of age. The adult mammalian cochlear sensory epithelium consists of mechanosensory hair cells and supporting cells but hair cells cannot regenerate. Here, the authors identify multipotent progenitors that arise from Eya1 -expressing otic cells that can regenerate hair cells in mice after 1 week of age.